Zur Stabilisierung medienbezogener Handlungsroutinen im Lehrer*innenberuf. Längsschnittliche Betrachtungen zur Integration von Tablets in den Arbeitsalltag - Dehmel, Lukas; Gerhardts, Lara; Meister, Dorothee M. (Mobile Medien im Schulkontext)

Online-Lehre 2020 – Eine medienwissenschaftliche Perspektive. Diskussionspapier Nr. 10 - Bohnenkamp, Björn; Burkhardt, Marcus; Grashöfer, Katja; Hlukhovych, Adrianna; Krewani, Angela; Matzner, Tobias; Missomelius, Petra; Shnayien, Marie-Luise

Explorations in Digital Cultures

Reparaturbetrieb, Inklusion und Fachkräftesicherung Transformation der Benachteiligtenförderung in Deutschland. - Heisler, Dietmar (Historische Berufsbildungsforschung Perspektiven auf Wissenschaftsgenese und -dynamik.)
Jeder Wissenschaftsdisziplin hilft ein Bewusstsein ihrer Geschichte und die Kenntnis ihrer Vielfalt, Paradigmen und Entwicklungsmöglichkeiten. Darauf basierend können Forschende ihr spezifisches Potential, Wissen und Handlungsrepertoire entfalten. Dabei ist Geschichtsschreibung und historische Berufsbildungsforschung immer zugleich selbst gefangen in ihrer je eigenen Zeit, beschränkt durch die Perspektiven der Personen, die sich an dem Rückblick beteiligen. Das macht Geschichte auch immer zur Geschichte der Herrschenden, die eine spezifische Perspektive und die mit ihr verbundene Forschung schreibend tradieren. Deshalb ist Vielfalt für die historische Berufsbildungsforschung so wertvoll, weil sie sich gegen verengte, eindimensionale Retrospektive stellt, gewissermaßen in die Ritzen und Fugen der Zeit schauen lässt. Basierend auf einer Tagung der Herausgeber im September 2019 zu „Retrospektiven, Perspektiven & Synergien einer Historischen Berufsbildungs- und Wissenschaftsforschung" an der Universität Rostock, entfaltet sich die Bandbreite der historischen Berufsbildungsforschung. Der Band vereint paradigmatische, mal stärker biografischen Zugänge sowie systemisch-gesellschaftspolitische und schließlich Analysen zur Genese der Wissenschaftsdisziplin. In den Beiträgen wird dem Einfluss von Einzelpersönlichkeiten und Forschungsparadigmen ebenso wie dem von Bildungssystemen am Beispiel der DDR, Skandinaviens und der bundesdeutschen Bildungspolitik nachgegangen. Vereint sind sowohl Beiträge zur Entstehung der Berufs- und Wirtschaftspädagogik, zur Rekonstruktion der Benachteiligtenförderung, Soziökonomie, Pflegedidaktik und Frauenforschung als auch Analysen berufsspezifischer Betrachtungen am Beispiel des Druckgewerbes, der Offiziere und der Ausbilder*innen.
Keywords: Benachteiligtenförderung; historische Berufsbildungsforschung; berufliche Förderung; Sozialpädagogik

(Un)Sicherheitsproduktion im Cyberspace. Cybersecurity-Architekturen in Deutschland und der Schweiz - Hälterlein, Jens (TATuP)

Lehrerkooperation und Digitalisierung - Gestaltung digital-kooperativer Arbeitsbeziehungen und der Stellenwert einer Fachlichkeitskonzeption von Lehrenden der Fächergruppe Erziehungswissenschaft - Engemann, Mario

Gero Fuchs: Gewinn als Umbruch der Ordnung? Der Fall des Siegburger Töpfers Peter Knütgen im 16. Jahrhundert, Tübingen 2019 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Laura Schmidt: Weihnachtliches Theater. Zur Entstehung und Geschichte einer bürgerlichen Fest- und Theaterkultur, Bielefeld 2017 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Inklusion und Intersektionalität im Kontext frühkindlicher Medienbildungsforschung. Sprachkulturelle Homogenität und Diversität sowie ihre Auswirkungen auf pädagogische Kommunikation in der Frühen Bildung - Günesli, Habib (QfI - Qualifizierung für Inklusion Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Dieser Beitrag basiert auf den Ergebnissen eines im Jahr 2019 abgeschlossenen Promotionsvorhabens im Rahmen des interventiv angelegten, in Dortmund angesiedelten, Forschungsprojekts KidSmart – Medienkompetent zum Schulübergang zu den Mediensozialisationsbedingungen von deutschen, deutsch-türkischen und deutsch-anderen vier und fünf Jahre alten Mädchen und Jungen in den sozialen Feldern Familie und Kita. Im vorliegenden Beitrag wird auf die Befragung der ErzieherInnen fokussiert, die mittels halbstandardisierter Fragebögen durchgeführt wurde. Untersucht wurde, wie sich der sprachlich-kulturelle Hintergrund der Kinder für das Kommunikationsverhalten der ErzieherInnen mit den Kindern in pädagogischer Anschlusskommunikation und in Gesprächen mit den Eltern der Kinder auswirkt. Hier wurde auch eine intersektionale Perspektive eingenommen und parallel zur Herkunftskultur auch das biologische Geschlecht der Kinder in die Auswertung einbezogen. Es stellte sich heraus, dass die Kommunikation sowohl mit den Kindern als auch mit den Eltern in Abhängigkeit der Herkunftskultur der Kinder und auch ihres Geschlechtes erfolgt. Pädagogisch ist zu fragen, inwiefern es den pädagogischen Fachkräften gelingt, benachteiligende Ausgangslagen auch tatsächlich auszugleichen und Partizipation im Sinne von Inklusion zu ermöglichen. Ausgehend von diesen Ergebnissen wird in diesem Beitrag die Bedeutung und Relevanz der Überschneidungen und Interdependenzen von Ungleichheitsdimensionen für eine inklusionsorientierte Qualifikation pädagogischer Fachkräfte in institutionell-frühkindlichen Medienbildungskontexten diskutiert. Konkret richtet sich der Blick auf die sprachlich-kulturelle Ein- und Vielfalt in den frühkindlichen Einrichtungen sowie die Wahrnehmungen und Einschätzungen der pädagogischen Fachkräfte, die sie in Hinblick auf die Kooperationswilligkeit der Eltern, die Anschlusskommunikation mit den Kindern und schließlich die medialen Fähig- und Fertigkeiten der Kinder äußern.

Regularizing neural networks with gradient monitoring - Chadha, Gavneet Singh; Meydani, Elnaz; Schwung, Andreas (Recent Advances in Big Data and Deep Learning: Proceedings of the INNS Big Data and Deep Learning Conference INNSBDDL2019, held at Sestri Levante, Genova, Italy 16-18 April 2019)

Probing nonclassicality with matrices of phase-space distributions - Bohmann, Martin; Agudelo, Elizabeth; Sperling, Jan (Quantum)
We devise a method to certify nonclassical features via correlations of phase-space distributions by unifying the notions of quasiprobabilities and matrices of correlation functions. Our approach complements and extends recent results that were based on Chebyshev's integral inequality \cite{BA19}. The method developed here correlates arbitrary phase-space functions at arbitrary points in phase space, including multimode scenarios and higher-order correlations. Furthermore, our approach provides necessary and sufficient nonclassicality criteria, applies to phase-space functions beyond s-parametrized ones, and is accessible in experiments. To demonstrate the power of our technique, the quantum characteristics of discrete- and continuous-variable, single- and multimode, as well as pure and mixed states are certified only employing second-order correlations and Husimi functions, which always resemble a classical probability distribution. Moreover, nonlinear generalizations of our approach are studied. Therefore, a versatile and broadly applicable framework is devised to uncover quantum properties in terms of matrices of phase-space distributions.

Classical evolution in quantum systems - Sperling, Jan; Walmsley, I A (Physica Scripta)

Transfer function replacement of phenomenological single-mode equations in semiconductor microcavity modeling - Carcamo, M.; Schumacher, Stefan; Binder, R. (Applied Optics)
Semiconductor microcavities are frequently studied in the context of semiconductor lasers and in application-oriented fundamental research on topics such as linear and nonlinear polariton systems, polariton lasers, polariton pattern formation, and polaritonic Bose–Einstein condensates. A commonly used approach to describe theoretical properties includes a phenomenological single-mode equation that complements the equation for the nonlinear optical response (interband polarization) of the semiconductor. Here, we show how to replace the single-mode equation by a fully predictive transfer function method that, in contrast to the single-mode equation, accounts for propagation, retardation, and pulse-filtering effects of the incident light field traversing the distributed Bragg reflector (DBR) mirrors, without substantially increasing the numerical complexity of the solution. As examples, we use cavities containing GaAs quantum wells and transition-metal dichalcogenides (TMDs).
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Chiral condensates in a polariton hexagonal ring. - Ma, Xuekai; Kartashov, YV; Kavokin, A; Schumacher, Stefan (Optics Letters)

Carbon vacancy-related centers in 3C-silicon carbide: Negative-U properties and structural transformation - von Bardeleben, H. J.; Rauls, E.; Gerstmann, Uwe (Physical Review B)

Electron paramagnetic resonance study of ferroelectric phase transition and dynamic effects in a Mn2+ doped [NH4][Zn(HCOO)3] hybrid formate framework - Navickas, Marius; Giriūnas, Laisvydas; Kalendra, Vidmantas; Biktagirov, Timur; Gerstmann, Uwe; Schmidt, Wolf Gero; Mączka, Mirosław; Pöppl, Andreas; Banys, Jūras; Šimėnas, Mantas (Physical Chemistry Chemical Physics)
EPR spectroscopy reveals the universality class and dynamic effects of the [NH4][Zn(HCOO)3] hybrid formate framework.

Spin-orbit driven electrical manipulation of the zero-field splitting in high-spin centers in solids - Biktagirov, Timur; Gerstmann, Uwe (Physical Review Research)
Keywords: General Engineering

Photocatalytic properties of graphene‐supported titania clusters from density‐functional theory - Badalov, Sabuhi; Wilhelm, René; Schmidt, Wolf Gero (Journal of Computational Chemistry)
Density-functional theory calculations of (TiO2)n clusters (n = 1–5) in the gas phase and adsorbed on pristine graphene as well as graphene quantum dots are presented. The cluster adsorption is found to be dominated by van der Waals forces. The electronic structure and in particular the excitation energies of the bare clusters and the TiO2/graphene composites are found to vary largely in dependence on the size of the respective constituents. This holds in particular for the energy and the spatial localization of the highest occupied and lowest unoccupied molecular orbitals. In addition to a substantial gap narrowing, a pronounced separation of photoexcited electrons and holes is predicted in some instances. This is expected to prolong the lifetime of photoexcited carriers. Altogether, TiO2/graphene composites are predicted to be promising photocatalysts with improved electronic and photocatalytic properties compared to bulk TiO2.

Accurate photon echo timing by optical freezing of exciton dephasing and rephasing in quantum dots - Kosarev, Alexander N.; Rose, Hendrik; Poltavtsev, Sergey V.; Reichelt, Matthias; Schneider, Christian; Kamp, Martin; Höfling, Sven; Bayer, Manfred; Meier, Torsten; Akimov, Ilya A. (Communications Physics)
Abstract Semiconductor quantum dots are excellent candidates for ultrafast coherent manipulation of qubits by laser pulses on picosecond timescales or even faster. In inhomogeneous ensembles a macroscopic optical polarization decays rapidly due to dephasing, which, however, is reversible in photon echoes carrying complete information about the coherent ensemble dynamics. Control of the echo emission time is mandatory for applications. Here, we propose a concept to reach this goal. In a two-pulse photon echo sequence, we apply an additional resonant control pulse with multiple of 2 π area. Depending on its arrival time, the control slows down dephasing or rephasing of the exciton ensemble during its action. We demonstrate for self-assembled (In,Ga)As quantum dots that the photon echo emission time can be retarded or advanced by up to 5 ps relative to its nominal appearance time without control. This versatile protocol may be used to obtain significantly longer temporal shifts for suitably tailored control pulses.

Realization of all-optical vortex switching in exciton-polariton condensates - Meier, Torsten; Ma, Xuekai; Berger, Bernd; Aßmann, Marc; Driben, Rodislav; Schneider, Christian; Höfling, Sven; Schumacher, Stefan (Nature communications)
Vortices are topological objects representing the circular motion of a fluid. With their additional degree of freedom, the vorticity, they have been widely investigated in many physical systems and different materials for fundamental interest and for applications in data storage and information processing. Vortices have also been observed in non-equilibrium exciton-polariton condensates in planar semiconductor microcavities. There they appear spontaneously or can be created and pinned in space using ring-shaped optical excitation profiles. However, using the vortex state for information processing not only requires creation of a vortex but also efficient control over the vortex after its creation. Here we demonstrate a simple approach to control and switch a localized polariton vortex between opposite states. In our scheme, both the optical control of vorticity and its detection through the orbital angular momentum of the emitted light are implemented in a robust and practical manner.